Electromagnetic wave absorbing particles, electromagnetic wave absorbing particle dispersion, method for manufacturing electromagnetic wave absorbing particles
Patent Information
- Application Number
- KR1020227020076
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-01-31
- Filing Date
- 2021-01-28
- Publication Date
- 2026-09-04
- Estimated Expiration
- 2041-01-28
Smart Images

Figure 112022061737024-PCT00003_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to electromagnetic wave absorbing particles, an electromagnetic wave absorbing particle dispersion, and a method for manufacturing electromagnetic wave absorbing particles. Background Technology
[0002] According to the 5th edition of the Dictionary of Physical and Chemical Sciences, "electromagnetic waves with wavelengths in the range of about 1 nm to 1 mm are called light." This wavelength range includes the visible light region and the infrared region.
[0003] Near-infrared rays contained in sunlight penetrate window materials and enter the interior, raising the surface temperatures of walls and floors, as well as the indoor air temperature. Conventionally, to maintain a comfortable indoor thermal environment, it has been practiced to prevent the indoor air temperature from rising by blocking near-infrared rays entering through windows, such as by using shading materials on window materials.
[0004] As a light-blocking material used for windows, etc., Patent Document 1 proposes a light-blocking film containing black fine powder containing inorganic pigments such as carbon black and titanium black, or organic pigments such as aniline black.
[0005] In addition, Patent Document 2 discloses a thermal sheet formed as a knitted fabric using a strip-shaped film having infrared reflectivity and a strip-shaped film having infrared absorbivity as warp or weft threads, respectively. It also describes using a synthetic resin film laminated with an aluminum deposition process and a synthetic resin film as the strip-shaped film having infrared reflectivity.
[0006] The applicant proposed in Patent Document 3 an infrared shielding material fine particle dispersion in which infrared material fine particles are dispersed in a medium, wherein the infrared material fine particles contain tungsten oxide fine particles or / and composite tungsten oxide fine particles, and the dispersion particle size of the infrared material fine particles is 1 nm or more and 800 nm or less. Prior art literature
[0007] Japanese Patent Publication No. 2003-029314, Japanese Patent Publication No. Hei 9-107815, International Publication No. 2005 / 037932
[0008] K. Adachi and T. Asahi, "Activation of plasmons and polarons in solar control cesium tungsten bronze and reduced tungsten oxide nanoparticles, "Journal of Material Research, Vol. 27, 965-970(2012)S. Yoshio and K. Adachi, "Polarons in reduced cesium tungsten bronzes studied using the DFT+U method, "Materials Research Express, Vol. 6, 026548(2019)K. Machida, M. Okada, and K. Adachi, "Excitations of free and localized electrons at nearby energies in reduced cesium tungsten bronze nanocrystals, "Journal of Applied Physics, Vol. 125, 103103(2019)S. F. Solodovnikov, N.V. Ivannikova, Z.A. Solodovnikova, E.S. Zolotova, "Synthesis and X-ray diffraction study of potassium, rubidium, and cesium polytungstates with defect pyrochlore and hexagonal tungsten bronze structures, "Inorganic Materials, Vol. 34, 845-853(1998)M. Okada, K. Ono, S. Yoshio, H. Fukuyama and K.Adachi, “Oxygen vacancies and pseudo Jahn-Teller destabilization in cesium-doped hexagonal tungsten bronzes,” Journal of American Ceramic Society, Vol. 102, 5386-5400(2019)S. Yoshio, M. Okada, K. Adachi, “Destabilization of Pseudo Jahn-Teller Distortion in Cesium-doped Hexagonal Tungsten Bronzes”, J. Appl. Phys., vol. 124, 063109-1-8 (2018). The problem to be solved
[0009] In the aforementioned patent document 3, tungsten oxide microparticles or / and composite tungsten oxide microparticles are disclosed as infrared shielding material microparticles. The transparent film in which these tungsten oxides are dispersed is accompanied by blue coloring, and the degree of blueness becomes stronger as the amount added increases.
[0010] However, in recent years, for applications such as automotive glass or photothermal conversion materials, there is a demand for a neutral color that increases near-infrared absorption—that is, lowers solar transmittance—while having no coloring such as blue in the transmitted color.
[0011] When based on a blue material such as the transparent film with dispersed tungsten oxide mentioned above, the colors obtained when coloring glass with various pigments or dyes are limited. In particular, it is difficult to obtain a yellow-based transparent color, which is a complementary color.
[0012] In addition, for photothermal conversion materials, specifically for applications such as bonding transparent resin members by photothermal conversion, a pure white color is required, but it is difficult to achieve a pure white color with materials such as the tungsten oxide mentioned above.
[0013] In contrast, for example, if the transmitted color of a dispersion such as a transparent film or dispersion in which a composite tungsten oxide is dispersed is made neutral, that is, transparent, the applications can be expanded. However, there have been no reports to date of a composite tungsten oxide that can achieve a neutral color while lowering the solar transmittance when used as a dispersion or dispersion.
[0014] Therefore, in one aspect of the present invention, the purpose is to provide electromagnetic wave absorbing particles that, when dispersed, suppress solar radiation transmittance while having a more neutral color tone for the transmitted color. means of solving the problem
[0015] In one aspect of the present invention, the general formula Cs x W 1-y O 3-z (0.2≤x≤0.4, 0 <y≤0.4, 0<z≤0.46)로 표시되고, 사방정 또는 육방정의 결정 구조를 구비한 세슘텅스텐산화물을 함유하는 전자파 흡수 입자를 제공한다. Effects of the invention
[0016] In one aspect of the present invention, electromagnetic wave absorbing particles can be provided that, when dispersed, suppress solar radiation transmittance while having a more neutral color tone. Brief explanation of the drawing
[0017] Fig. 1a shows cesium tungsten oxide (Cs4W 11 O 35 This is an explanatory diagram of the crystal structure of ). Fig. 1b shows cesium tungsten oxide (Cs4W 12 O 36 This is an explanatory diagram of the crystal structure of ). FIG. 2a shows cesium tungsten oxide (Cs4W 11 O 35 It is the energy band structure of ). Fig. 2b shows cesium tungsten oxide (Cs4W 12 O 36 It is the energy band structure of ). FIG. 2c shows cesium tungsten oxide (Cs4W 11 O 36 It is the energy band structure of ). FIG. 2d shows cesium tungsten oxide (Cs6W 17 O 54 It is the energy band structure of ). Figure 3a is the dielectric function of cesium tungsten oxide. Figure 3b is the dielectric function of cesium tungsten oxide. Figure 4 is an electron beam diffraction image taken from the c-axis direction of powder A' obtained in Example 1. FIG. 5 is
[0001] of the pseudo-hexagonal particles of powder A obtained in Example 1. HEX It is an electron beam diffraction pattern along the normal axis. Figure 6 is a STEM-HAADF phase observed from the
[0221] normal axis of the pseudo-hexagonal particles of powder A obtained in Example 1. FIG. 7 shows the
[0001] pseudo-hexagonal particles of powder B obtained in Example 2. HEX It is an electron beam diffraction pattern along the normal axis. FIG. 8 is
[0001] of the pseudo-hexagonal particles of powder C obtained in Example 3 HEX It is an electron beam diffraction pattern along the normal axis. FIG. 9a is the molar absorption coefficient of the dispersion prepared in Examples 14 to 20 and Comparative Example 1. FIG. 9b shows the molar absorption coefficients of the dispersions prepared in Examples 14 to 20 and Comparative Example 1. FIG. 9c is the molar absorption coefficient of the dispersion prepared in Examples 15, 16, 18, 22, 23 and Comparative Example 1. FIG. 10a is a transmittance profile of the dispersion prepared in Examples 15, 16, 19 and Comparative Examples 1 to 3, derived such that VLT becomes constant. FIG. 10b is a transmittance profile of the dispersion prepared in Examples 15, 16, 19 and Comparative Examples 1 to 3, derived so that VLT becomes constant. FIG. 11a is an explanatory diagram of the change in near-infrared absorption characteristics of dispersions related to Comparative Examples 1 to 3, Example 15, Example 16, and Example 19 over reduction time. FIG. 11b is an explanatory diagram of the change in near-infrared absorption characteristics of dispersions related to Comparative Examples 1 to 3, Example 15, Example 16, and Example 19 over reduction time. FIG. 11c is an explanatory diagram of the changes accompanying the color index and reduction time of the dispersions related to Comparative Examples 1 to 3, Example 15, Example 16, and Example 19. FIG. 11d is an explanatory diagram of the changes accompanying the color index and reduction time of the dispersions related to Comparative Examples 1 to 3, Example 15, Example 16, and Example 19. Specific details for implementing the invention
[0018] Hereinafter, embodiments for carrying out the present invention will be described with reference to the drawings, but the present invention is not limited to the following embodiments, and various modifications and substitutions can be made to the following embodiments without departing from the scope of the present invention.
[0019] [Electromagnetic wave absorbing particles, method for manufacturing electromagnetic wave absorbing particles]
[0020] The electromagnetic wave absorbing particles of the present embodiment and the method for manufacturing the electromagnetic wave absorbing particles are described.
[0021] (Electromagnetic wave absorbing particles)
[0022] The transmission color of cesium-doped hexagonal tungsten bronze nanoparticles, which have been used as electromagnetic wave absorbing particles in the past, is determined by their dielectric function hub (ε2) (ε2 obtained from experiments is disclosed in Non-Patent Literature 1), and band structure (Non-Patent Literature 2).
[0023] In the energy range of visible light (1.6 eV to 3.3 eV), cesium-doped hexagonal tungsten bronze (hereinafter abbreviated as Cs-HTB) has a sufficiently large band gap. Furthermore, since electron transitions between dd orbitals of tungsten are prohibited by the Fermi golden ratio, the probability of electron transitions is reduced, and ε2 takes a small value. Since ε2 represents the absorption of photons by electrons, visible light transmittance occurs when ε2 is small at visible wavelengths. However, near the blue wavelength, which is the shortest wavelength in the visible light region, absorption due to inter-band transitions exists, and near the red wavelength, which is the longest wavelength, localized surface plasmon resonance (LSPR) absorption and polaric electron transition absorption exist (Non-patent Literature 3). For this reason, light transmittance is constrained in each case.
[0024] As described above, in Cs-HTB, the band gap is sufficiently large, so the inter-band transition becomes greater than the energy of blue wavelength light, resulting in high blue transmittance. Conversely, on the red wavelength side, Cs-HTB has many conduction electrons, so LSPR absorption and polaronic absorption become strong, and at the same time, since the absorption wavelength approaches the red wavelength side, transmittance is low. Therefore, the transmitted color of the Cs-HTB nanoparticle dispersion film appears blue.
[0025] In other words, to neutralize the transmission color of the blue spectrum of Cs-HTB, it is necessary to strengthen the absorption on the blue side and strengthen the transmission on the red side. To do this, it is desirable to shift the absorption position of the inter-band transition to a low energy, and also to weaken the LSPR absorption and polaronic absorption to shift them to the low energy side.
[0026] To weaken LSPR absorption or polaronic absorption, it is effective to reduce the amount of free electrons and bound electrons contained in the material.
[0027] The aforementioned increase in absorption on the blue side is realized by using a material with a different energy band structure having a band gap at low energy as a base. In addition, transmission on the red side is due to cesium ions (Cs₂), which are the source of free or bound electrons. + ) or oxygen vacancies (V O The amount of ) can be controlled by adding or subtracting.
[0028] Based on the above considerations, the inventors of the present invention examined various cesium tungsten oxides, which are oxides containing cesium (Cs) and tungsten (W), and discovered that when electromagnetic wave absorbing particles containing cesium tungsten oxide obtained by reducing a crystal powder of a cesium tungsten oxide precursor nCs2O·mWO3 (n, m are integers, 3.6≤m / n≤9.0) containing Cs and W are used, the color tone of an electromagnetic wave absorbing particle dispersion such as a dispersed transparent film or an electromagnetic wave absorbing particle dispersion liquid is reduced in blueness and neutralized.
[0029] The above electromagnetic wave absorbing particle starts from a blue compound with low transmittance and a band gap narrower than hexagonal Cs-HTB, and by reducing this, V O It is thought that the hue was neutralized by gradually increasing the LSPR absorption and polaronic absorption within an allowable range to optimize the red transmittance.
[0030] In the above cesium tungsten oxide precursor nCs2O·mWO3 containing Cs, the charges of the positive elements Cs and W are neutralized by O, making it a non-conductive material. Cs2W7O 22 , Cs6W 20 O 63 , Cs2W6O 19 , Cs4W 11 O 35 , Cs6W 11 O 36 , Cs2W3O 10 For compounds listed in the WO3-Cs2O line, since the valence is balanced, the Fermi energy E FIt exists between the valence band and the conduction band and is nonconductive. When the Cs / W ratio (molar ratio) is 0.2 or greater, in order to accommodate Cs with a large ionic radius, the basic framework formed by the WO octahedron is either a hexagonal symmetric structure with large hexagonal vacancies, or a crystal structure in which plane defects containing W defects (tungsten defects) are formed in the atomic arrangement of hexagonal or cubic (pyrochlore structure) with large hexagonal vacancies, resulting in orthorhombic or monoclinic symmetry.
[0031] For example, in 2Cs2O·11WO3, in the model of Solodovnikov 1998 (non-patent document 4), in the hexagonal arrangement of WO octahedra similar to hexagonal tungsten bronze, a plane with W and O missing at a b / 8 pitch of the orthorhombic unit cell is inserted into the hexagonal (110) plane (=orthorhombic (010) plane), so the whole is orthorhombic. In these cesium tungsten oxide precursors nCs2O·mWO3 (n and m are integers, 3.6≤m / n≤9.0), the band gap is narrower than that of Cs-HTB, and therefore the transmittance of blue is low. However, it was found that when this is heated and reduced, the whole gradually changes into the hexagonal structure of tungsten bronze, and in the process, the band structure changes and the band gap widens, so the absorption of blue weakens, and thus the transmittance of blue becomes stronger. Furthermore, at this time, as reduction proceeds, electrons are gradually injected into the conduction band to become a conductor, and the band gap gradually widens due to the Burstein-Moss effect, so the transmission of blue light becomes stronger.
[0032] When the orthorhombic crystal becomes hexagonal by heat reduction, the plane defects containing W defects in the orthorhombic crystals gradually disappear, and a hexagonal framework of WO octahedrons is formed. The plane defects containing W defects are (010) ORTH It exists on a plane, which is a hexagonal prism plane {100} HEX , that is, [(100) HEX ,(010) HEX ,(110)HEX Since it is inherited from ], gradually {100} with heating and reduction HEX It becomes a hexagon containing defects on the face. The hexagon in this case is {100} HEX Because it contains defects in the planes, it deviates from perfect hexagonal symmetry and is in a state that can also be called pseudo-hexagonal. In this way, with heating and reduction, the crystal structure changes from orthorhombic to pseudo-hexagonal, and further to hexagonal. At this time, (010) containing the W defect that was contained in the orthorhombic structure ORTH The surface defect of the surface is, {100} HEX It is thought that it will be inherited by surface defects, gradually decrease, and eventually disappear.
[0033] Along with changes in crystal structure during thermal reduction, the electronic structure also changes. The disappearance of W defects results in the injection of a large amount of electrons into the material. In orthorhombic crystals, Cs outer shell electrons are consumed for the neutralization of O, making the material overall charge-neutral; however, when W defects are reduced to form a pseudo-hexagonal crystal, six outer shell electrons per W atom are consumed for the neutralization of O, causing Cs outer shell electrons to enter the W-5d orbital below the conduction band and become free electrons. These free electrons cause the absorption of near-infrared radiation through LSPR absorption. Meanwhile, thermal reduction simultaneously V O There is a function that generates. V O The generation of is carried out at a random site. V O When this occurs, the W atoms on either side become excess charge, and W 5+Localized electrons are generated that are bound (Non-patent Literature 2). These localized electrons transition to voids in the upper conduction band, causing polaronic absorption, and some are excited into free electron orbits, causing LSPR absorption (Non-patent Literature 3). Since the peak wavelengths of both these free electrons and bound electrons are near-infrared, the ends of the absorption fall within the red wavelength range, thereby lowering red transmittance. As the amount of free electrons and bound electrons increases—that is, as the degree of reduction increases—the wavelengths of LSPR absorption and polaronic absorption shift to higher wavelengths, and the amount of absorption increases, so red transmittance decreases.
[0034] Therefore, by reducing the crystal powder of the cesium tungsten oxide precursor nCs2O·mWO3 (n, m are integers, 3.6≤m / n≤9.0) and adjusting the degree of reduction at that time, the blue transmitted color can be neutralized.
[0035] The electromagnetic wave absorbing particles of the present embodiment described above can be produced by heating a crystal powder of a cesium tungsten oxide precursor nCs2O·mWO3 containing Cs and W in a reducing atmosphere of 650°C or higher and 950°C or lower. In the formula for the cesium tungsten oxide, n and m are integers, and it is preferable that 3.6 ≤ m / n ≤ 9.0 is satisfied.
[0036] That is, as electromagnetic wave absorbing particles, particles obtained by heating and reducing a crystal powder of a cesium tungsten oxide precursor nCs2O·mWO3 (n, m are integers, 3.6≤m / n≤9.0) containing cesium and tungsten in a reducing gas atmosphere at a temperature of 650°C or higher and 950°C or lower can be used.
[0037] In order for all or part of the material to become hexagonal tungsten bronze by heating and reduction, the value of m / n must be in the range of 3.6 ≤ m / n ≤ 9.0 as described above. If it is less than 3.6, it becomes a cubic pyrochlore phase after heating and reduction, exhibiting strong coloration and no near-infrared absorption. Furthermore, if it is greater than 9.0, it undergoes phase separation into hexagonal tungsten bronze and tungsten trioxide after heating and reduction, and the near-infrared absorption effect is significantly reduced. The above cesium tungsten oxide precursor is Cs4W with m / n = 5.5. 11 O 35 It is more desirable that it be Cs4W as an electromagnetic wave absorbing particle, as a columnar phase. That is, as an electromagnetic wave absorbing particle, as a columnar phase 11 O 35 It is more preferable to use particles obtained by heating and reducing a cesium tungsten oxide precursor containing a phase at a temperature of 650°C or higher and 950°C or lower in a reducing gas atmosphere. Cs4W 11 O 35 By using electromagnetic wave absorbing particles obtained by high-temperature reduction, when the said electromagnetic wave absorbing particles are dispersed, a large near-infrared absorption effect is obtained while having a transmitted color with suppressed blue tint. In addition, the main phase referred to here means the phase that is contained in the largest amount by mass ratio.
[0038] As described above, the heating temperature for reducing cesium tungsten oxide is preferably 650°C or higher and 950°C or lower. By setting the temperature to 650°C or higher, the structural change from orthorhombic to hexagonal is sufficiently carried out, thereby enhancing the near-infrared absorption effect. Furthermore, by setting the temperature to 950°C or lower, the speed of the crystal structure change is appropriately maintained, allowing for easy control into appropriate crystalline and electronic states. Additionally, if the heating temperature is higher than 950°C and reduction is carried out too excessively, lower oxides such as W metal or WO2 may be generated, which is also undesirable from a related perspective.
[0039] And, the electromagnetic wave absorbing particle of the present embodiment is of the general formula Cs x W 1-y O 3-z (0.2≤x≤0.4, 0 <y≤0.4, 0<z≤0.46)로 표시되고, 사방정 또는 육방정의 결정 구조를 구비한 세슘텅스텐산화물을 함유할 수 있다.
[0040] When the cesium tungsten oxide contained in the electromagnetic wave absorbing particles satisfies the above general formula such that the degree of W deficiency or oxygen vacancy Vo is within an appropriate range and is dispersed to form an electromagnetic wave absorbing particle dispersion, the solar radiation transmittance can be suppressed while the transmitted color can be made to a more neutral hue.
[0041] In addition, the electromagnetic wave absorbing particles may include the above-mentioned composite tungsten oxide. However, even in this case, it is not excluded that they contain unavoidable impurities that are mixed in during the manufacturing process, etc.
[0042] Conventionally known tungsten bronze for electromagnetic wave absorption has a hexagonal structure. Meanwhile, the composite tungsten oxide of the electromagnetic wave absorbing particle of the present embodiment may have an orthorhombic or hexagonal crystal structure. Furthermore, the hexagonal structure described herein includes pseudo-hexagonal structures.
[0043] The composite tungsten oxide containing the electromagnetic wave absorbing particles preferably has linear or planar defects on one or more planes selected from the orthorhombic (010) plane, the hexagonal prism plane {100} plane, and the hexagonal basal plane (001). The defects include stacking irregularities based on misalignment between planes, or disturbances in the arrangement or atomic positions of Cs atoms or W atoms within the planes, and thus sometimes involve streaks in the electron beam diffraction spots. The hexagonal prism plane {100} plane refers to the (100) plane, the (010) plane, and the (110) plane. The defects associated with the composite tungsten oxide, namely lattice defects, involve at least a W defect, specifically a partial W defect, and this W defect causes a loss of electrons in the crystal, and as previously explained, this acts as one of the essential causes for the neutralization of the blue tone.
[0044] Cesium tungsten oxide has defects, and the related defects may include tungsten defects as described above.
[0045] Furthermore, it is also possible for some of the oxygen atoms in the WO octahedra, which constitute the orthorhombic or hexagonal crystals that form the basic structure of cesium tungsten oxide, to be more randomly missing. These vacancies of octahedral oxygen, V O As mentioned above, it is introduced randomly, and the known hexagonal tungsten bronze Cs 0.32 WO 3-y In this case, it is known that y=0.46 or O reaches up to 15% of the electric charge point (Non-patent document 5). General formula Cs representing the cesium tungsten oxide contained in the electromagnetic wave absorbing particles of the present embodiment. x W 1-y O 3-z In this case, the maximum amount V of z=0.46 O It can include. That is, z can be 0.46 or less.
[0046] The lattice constant of the cesium tungsten composite oxide corresponds to the amount of defects, composition, and crystallinity within the crystal lattice. While the value of the a-axis shows variation with respect to these variables, the value of the c-axis corresponds relatively well to the amount of lattice defects or optical properties. Consequently, it is preferable that the cesium tungsten oxide contained in the electromagnetic wave absorbing particles of the present embodiment has a c-axis length in hexagonal terms of 7.560 Å or more and 7.750 Å or less. By setting the c-axis length in hexagonal terms of the cesium tungsten oxide to the above range, the near-infrared absorption effect is sufficiently enhanced, and the visible light transmittance is particularly enhanced. Furthermore, if the cesium tungsten oxide is hexagonal, the conversion is unnecessary, and the c-axis length in that hexagonal form becomes the c-axis length in hexagonal terms.
[0047] The cesium tungsten oxide contained in the electromagnetic wave-absorbing particles of the present embodiment is often identified as a mixed phase of orthorhombic and hexagonal phases when the diffraction pattern of the sample is measured by X-ray powder diffraction. For example, Cs4W 11 O 35 If the raw material is reduced, orthorhombic Cs4W 11 O 35 and hexagonal Cs 0.32 It is identified with the mixed phase of WO3. In this case, the lattice constants of each phase can be determined using Rietveld analysis or the like, and converted into hexagonal equivalent values. As previously explained, since the orthorhombic phase is a hexagonal phase with lattice defect planes, the orthorhombic lattice constants can be converted into hexagonal lattice constants by an appropriate lattice correspondence model. If the correspondence of lattice changes between orthorhombic and hexagonal phases is assumed to be the model of Solodovnikov 1998 (Non-patent Literature 4), from the geometric relationship for this model, 4a orth 2 +b orth 2 =64a hex 2 =64b hex 2 , c orth =c hexSince the relationship is extracted, all hexagonal converted lattice constants can be obtained using these equations. In addition, a in the above equation orth , b orth , c orth represents the lengths of the a-axis, b-axis, and c-axis of an orthorhombic shape. Also, a hex , b hex , c hex represents the lengths of the a-axis, b-axis, and c-axis of the hexagon.
[0048] The cesium tungsten oxide contained in the electromagnetic wave absorbing particles of the present embodiment may have a portion of Cs substituted by an additive element. In this case, it is preferable that the additive element be one or more selected from Na, Tl, In, Li, Be, Mg, Ca, Sr, Ba, Al, and Ga.
[0049] The above-mentioned additive elements are electron-donating and assist in electron donation to the conduction band of the WO octahedral framework at the Cs site.
[0050] The average particle size of the electromagnetic wave absorbing particles of the present embodiment is not particularly limited, but it is preferably 0.1 nm or larger and 200 nm or smaller. This is because by making the average particle size of the electromagnetic wave absorbing particles 200 nm or smaller, localized surface plasmon resonance is expressed more significantly, which allows for particularly enhanced near-infrared absorption characteristics, that is, particularly suppressed solar radiation transmittance. In addition, by making the average particle size of the electromagnetic wave absorbing particles 0.1 nm or larger, it can be manufactured easily industrially. Furthermore, the particle size is closely related to the color of the electromagnetic wave absorbing particle dispersion, such as a dispersion-transmitting film in which the electromagnetic wave absorbing particles are dispersed, and in the particle size range where Mie scattering is dominant, short-wavelength scattering in the visible light region decreases as the particle size becomes smaller. Therefore, increasing the particle size has the effect of suppressing the blue tint, but if it exceeds 100 nm, the film haze accompanying light scattering becomes too large to be ignored, and if it exceeds 200 nm, in addition to the increase in film haze, the generation of surface plasmons is suppressed, so the LSPR absorption becomes excessively small.
[0051] Here, the average particle size of the electromagnetic wave absorbing particles can be determined from the median diameter of a plurality of electromagnetic wave absorbing particles measured from a transmission electron microscope, or from the dispersion particle size measured by a particle size measuring device based on the dynamic light scattering method of the dispersion.
[0052] In addition, when applied to applications where transparency in the visible light region is particularly important, such as the front glass of an automobile, it is desirable to additionally consider scattering reduction by electromagnetic wave absorbing particles. When such scattering reduction is important, it is particularly desirable that the average particle size of the electromagnetic wave absorbing particles be 30 nm or less.
[0053] The average particle size refers to the particle size at 50% of the accumulated value in the particle size distribution, and the average particle size has the same meaning in other parts of this specification. As a method for measuring the particle size distribution to calculate the average particle size, direct measurement of the particle size of each particle using, for example, a transmission electron microscope may be used. In addition, the average particle size may be measured by a particle size measuring device based on the dynamic light scattering method of a dispersion as described above.
[0054] In addition, the electromagnetic wave absorbing particles may be surface-treated for purposes such as surface protection, improved durability, prevention of oxidation, and improved water resistance. Although the specific details of the surface treatment are not particularly limited, for example, the surface of the electromagnetic wave absorbing particles of the present embodiment may be modified with a compound containing one or more atoms selected from Si, Ti, Zr, and Al. In this case, one or more compounds selected from oxides, nitrides, carbides, etc., may be examples of compounds containing one or more atoms (elements) selected from Si, Ti, Zr, and Al.
[0055] Here, the band structures of cesium tungsten oxide and cesium tungsten oxide precursors are described.
[0056] As explained above, it was shown that reducing nCs2O·mWO3 (n, m are integers, 3.6≤m / n≤9.0) at high temperatures yields a solar radiation shielding material with a transmittance color closer to neutral. During high-temperature reduction, hexagonalization including the elimination of W defects and V O It is thought that electrons are injected into the conduction band through the generation of [this], which is the source of near-infrared absorption, and this change in electronic structure is supported by first-principles calculations.
[0057] Cs4W in Fig. 1a 11 O 35 The crystal structure of is illustrated. Also, Cs in Fig. 1b 0.33 WO3 in Cs4W12 O 36 The crystal structure of is illustrated. In FIGS. 1a and 1b, cesium (11) and oxygen (12) are illustrated. Additionally, the same hatching is assigned to atoms of the same type. Tungsten is not illustrated in FIGS. 1a and 1b because it is placed within an octahedron formed of oxygen (12). FIG. 1b is Cs 0.33 WO3, Cs4W of FIG. 1a 11 O 35 It is a structure that takes a new axis in a four-sided shape to allow for comparison.
[0058] Cs4W in Fig. 1a 11 O 35 The structure is the Cs4W in Fig. 1b 12 O 36 In the crystal structure of, W and O are regularly missing.
[0059] The band structures of the cesium tungsten oxide crystal structures of FIGS. 1a and 1b are illustrated in FIGS. 2a and 2b, respectively. In addition, the Cs4W of FIG. 1b 12 O 36 Based on, Cs4W with 1 W missing 11 O 36 Cs6W with a band structure, and 1.5 times the cell size in the b-axis direction, with one W missing 17 O 54 The structure of each band is illustrated in Fig. 2c and Fig. 2d, respectively.
[0060] Cs4W illustrated in FIGS. 2a and 2b 11 O 35 band structure, and Cs4W 12 O 36 The band structure is similar, but the Fermi energy (E F The former is within the band gap, and the latter is below the conduction band. Therefore, Cs4W 11 O 35 is an insulator, and Cs4W 12 O 36 It is a conductor. Cs4W 11 O35 In Cs4W 12 O 36 Based on this, there is a shortage of 1 unit each of W and O in the unit cell. Cs4W is full of W and O. 12 O 36 In this case, it is interpreted that a hexagonal WO3 network is formed and Cs electrons are injected into the W-5d orbital to become a conductor (Non-patent Literature 6).
[0061] Cs4W in Fig. 2c 11 O 36 Silver, Cs4W in Fig. 2b 12 O 36 It is a structure obtained by subtracting 1 from W.
[0062] Cs6W in Fig. 2d 17 O 54 , that is, 3Cs2O·17WO3 is Cs4W in Fig. 2b 12 O 36 , that is, Cs6W 18 O 54 From the perspective, it is a structure that maintains charge neutrality while subtracting one W.
[0063] The amount of W defect decreases in the order of Fig. 2a, Fig. 2d, and Fig. 2b, and E F The electrons are rising sequentially to the bottom side of the conductor, and as W electrons are injected into the W-5d orbital, the number of conduction electrons increases, supporting the increase in near-infrared absorption.
[0064] Cs4W 12 O 36 In the case where O is missing, detailed calculation examples have already been reported, and it is known that free electrons and localized electrons increase significantly along with the introduction of localized orbitals at the bottom of the conduction band (Non-patent document 2).
[0065] In experimentally obtained pseudo-hexagonal structures (intermediate structures during the phase transition between orthorhombic and hexagonal), the electronic state is considered to be a mixture of the above elements. That is, accompanying reduction, hexagonalization involving the disappearance of the W deficiency and V ODue to the generation of, electrons are gradually injected into the conduction band, and Fermi energy E F It rises from the band gap to the lower part of the conduction band.
[0066] Based on these band structures, the results of calculating the dielectric function including the Drude term are shown in FIGS. 3a and 3b. Focusing on the position of ε1=0 in the dielectric function ε1 shown in FIG. 3b, the shielded plasma frequency (Ω SP ) is Cs4W 11 O 35 , Cs6W 17 O 54 , Cs4W 12 O 36 , Cs4W 12 O 35 It can be seen that it increases in this order. Near-infrared absorption is expected to increase in this order, and this trend is consistent with the observation results.
[0067] From the dielectric function ε2 plot shown in FIG. 3a, it can be seen that the ε2 in the visible region is generally small for cesium tungsten oxide. At 3.3 eV in the blue region indicated by the dashed line (31), the band gap is narrow, defined by the inter-band transition, for Cs4W 11 O 35 I'm CS6W 17 O 54 The absorption of increases. Meanwhile, at 1.6 eV in the red region indicated by the dotted line (32), influenced by the end of surface plasmon absorption, Cs4W 12 O 35 It can be seen that the absorption is large. The transmitted light in the red region is Ω SPIt is expected to decrease in the order of decreasing. The profile of ε2 in the visible light region illustrated in Fig. 3a basically corresponds to the experimentally observed Fig. 9b and accurately reproduces that trend. That is, compared to the conventionally used cesium tungsten oxide, the reason for the decrease in blueness in the cesium tungsten oxide containing electromagnetic wave absorbing particles suitable for use in the electromagnetic wave absorbing particle dispersion of this embodiment is that nCs2O·mWO3 (3.6≤m / n≤9.0), which has deficiencies in W and O, was used as a raw material, thereby reducing the Cs containing W deficiencies. 0.33 W 1-y O 3-z It is thought that this is because a phase is formed, and absorption on the high-energy side increases. By controlling the high-temperature reduction of nCs2O·mWO3 (3.6≤m / n≤9.0), the band gap and the amount of electrons injected into the conduction band are controlled, allowing for the control of a bluish tint. In addition, it was confirmed that the near-infrared absorption effect at that time remains relatively high.
[0068] (Method for manufacturing electromagnetic wave absorbing particles)
[0069] The method for manufacturing electromagnetic wave absorbing particles of the present embodiment is not particularly limited, and any method capable of manufacturing electromagnetic wave absorbing particles satisfying the characteristics already described can be used without particular limitation. Hereinafter, one configuration example of the method for manufacturing electromagnetic wave absorbing particles is described.
[0070] The method for manufacturing electromagnetic wave absorbing particles of the present embodiment may, for example, have the following process.
[0071] A process for synthesizing a cesium tungsten oxide precursor, which is a tungstate containing cesium.
[0072] A heating and reduction process for heating and reducing a cesium tungsten oxide precursor in a reducing gas atmosphere at a temperature of 650°C or higher and 950°C or lower.
[0073] The following describes each process.
[0074] (1) Cesium tungsten oxide precursor synthesis process
[0075] In the process of synthesizing a cesium tungsten oxide precursor, a cesium tungsten oxide precursor containing cesium, namely cesium tungsten, can be synthesized. If a cesium tungsten oxide precursor has already been synthesized, the method for manufacturing electromagnetic wave absorbing particles according to the present embodiment may be initiated from a heating reduction process.
[0076] In addition, the cesium tungstate oxide precursor, which is a cesium tungstate, is preferably a crystalline powder of nCs2O·mWO3 (n, m is an integer, 3.6≤m / n≤9.0). As for the cesium tungstate oxide precursor, it is more preferable that it be a stable cesium tungstate. As for a stable cesium tungstate, Cs4W 11 O 35 , Cs2W6O 19 , Cs6W 20 O 63 , Cs2W7O 22 , Cs6W 11 O 36 One or more types selected from the above may be cited. The cesium tungsten oxide precursor is particularly Cs4W as the main phase. 11 O 35 It is more preferable that the cesium tungsten oxide precursor contains a phase.
[0077] These cesium tungstates can be prepared, for example, by calcining a mixture of raw material powders containing cesium or tungsten in the atmosphere at a temperature of 700°C or higher and 1000°C or lower. In addition, the method of manufacturing cesium tungstates is not limited to the above forms, and other methods such as the sol-gel method or complex polymerization method may also be used.
[0078] In addition, as cesium tungstate used as a starting material, non-equilibrium tungstate obtained by vapor phase synthesis, etc., may be used. This includes powders produced by thermal plasma magic or powders produced by electron beam melting.
[0079] (2) Heating and reducing process
[0080] A cesium tungsten oxide precursor as the above-mentioned starting material, specifically, a cesium tungstate having one or more crystal structures selected from, for example, orthorhombic, monoclinic, and pseudo-hexagonal, can be provided to a heating reduction process.
[0081] In the heating and reduction process, the above-described cesium tungsten oxide precursor can be heated and reduced in a reducing gas atmosphere at a temperature of 650°C or higher and 950°C or lower. By carrying out the heating and reduction process, electromagnetic wave absorbing particles containing cesium tungsten oxide of a desired composition are obtained.
[0082] When performing a heat reduction treatment, it is preferable to perform it under a stream of reducing gas. As the reducing gas, a mixed gas containing a reducing gas such as hydrogen and one or more inert gases selected from nitrogen, argon, etc. may be used. In addition, heating in a steam atmosphere or vacuum atmosphere, or other mild heating and reduction conditions may be used in combination.
[0083] In addition, the method for manufacturing electromagnetic wave absorbing particles of the present embodiment is not particularly limited to the above form. As a method for manufacturing electromagnetic wave absorbing particles, various methods capable of forming a predetermined structure including a defective microstructure can be used. Examples of methods for manufacturing electromagnetic wave absorbing particles include a method of reducing tungstate obtained by a solid-phase method, a liquid-phase method, or a gas-phase method, or a method of reducing WO3 in molten alkali halide.
[0084] The method for manufacturing electromagnetic wave absorbing particles may also have any process.
[0085] (3) Grinding process
[0086] As previously explained, it is desirable for the electromagnetic wave absorbing particles to be micronized and become fine particles. For this reason, the method for manufacturing electromagnetic wave absorbing particles may include a grinding process for grinding the powder obtained by a heating reduction process.
[0087] The specific means for grinding and micronizing are not particularly limited, and various means capable of mechanical grinding may be used. As for the mechanical grinding method, a dry grinding method using a jet mill or the like may be used. Additionally, mechanical grinding may be performed in a solvent during the process of obtaining the electromagnetic wave absorbing particle dispersion described later. In this case, since the electromagnetic wave absorbing particles are dispersed in a liquid medium during the grinding process, it may also be referred to as a grinding and dispersion process.
[0088] (4) Formula process
[0089] As previously explained, the electromagnetic wave absorbing particle may have its surface modified with a compound containing one or more atoms selected from Si, Ti, Zr, and Al. Thus, the method for manufacturing the electromagnetic wave absorbing particle may further include, for example, a modification process in which the electromagnetic wave absorbing particle is modified with a compound containing one or more atoms selected from Si, Ti, Zr, and Al.
[0090] In the modification process, the specific conditions for modifying the electromagnetic wave absorbing particles are not particularly limited. For example, a modification process may be performed in which an alkoxide containing one or more atoms selected from the above atomic group (metal group) is added to the electromagnetic wave absorbing particles to be modified, and a film is formed on the surface of the electromagnetic wave absorbing particles.
[0091] [Electromagnetic wave absorbing particle dispersion]
[0092] Next, an example of the composition of the electromagnetic wave absorbing particle dispersion of the present embodiment will be described.
[0093] The electromagnetic wave absorbing particle dispersion of the present embodiment may include the electromagnetic wave absorbing particles described above and one or more liquid media selected from water, organic solvents, oils and fats, liquid resins, and liquid plasticizers. It is preferable that the electromagnetic wave absorbing particle dispersion has a composition in which electromagnetic wave absorbing particles are dispersed in a liquid medium.
[0094] As for the liquid medium, one or more types selected from water, organic solvents, oils and fats, liquid resins, and liquid plasticizers can be used, as previously explained.
[0095] As organic solvents, various types can be selected, such as alcohol-based, ketone-based, hydrocarbon-based, glycol-based, and water-based solvents. Specifically, alcohol-based solvents such as isopropyl alcohol, methanol, ethanol, 1-propanol, isopropanol, butanol, pentanol, benzyl alcohol, diacetone alcohol, and 1-methoxy-2-propanol; ketone-based solvents such as dimethyl ketone, acetone, methyl ethyl ketone, methyl propyl ketone, methyl isobutyl ketone, cyclohexanone, and isophorone; ester-based solvents such as 3-methyl methoxy-propionate and butyl acetate; and glycol derivatives such as ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol isopropyl ether, propylene glycol monomethyl ether, propylene glycol monoethyl ether, propylene glycol methyl ether acetate, and propylene glycol ethyl ether acetate; One or more types selected from amides such as formamide, N-methylformamide, dimethylformamide, dimethylacetamide, N-methyl-2-pyrrolidone; aromatic hydrocarbons such as toluene and xylene; and halogenated hydrocarbons such as ethylene chloride and chlorbenzene may be cited.
[0096] However, among these, organic solvents with low polarity are preferred, and in particular, isopropyl alcohol, ethanol, 1-methoxy-2-propanol, dimethyl ketone, methyl ethyl ketone, methyl isobutyl ketone, toluene, propylene glycol monomethyl ether acetate, n-butyl acetate, etc. are more preferred. One or more of these organic solvents may be used.
[0097] As for the oil, one or more types selected from drying oils such as linseed oil, sunflower oil, and tung oil; semi-drying oils such as sesame oil, cottonseed oil, rapeseed oil, soybean oil, and rice bran oil; non-drying oils such as olive oil, coconut oil, palm oil, and dehydrated castor oil; fatty acid monoesters obtained by directly esterifying a fatty acid of vegetable oil with a monoalcohol; ethers; and petroleum-based solvents such as Isofa (registered trademark) E, Exol (registered trademark) Hexane, Heptane, E, D30, D40, D60, D80, D95, D110, and D130 (all manufactured by ExxonMobil).
[0098] As for the liquid resin, one or more types selected from, for example, liquid acrylic resin, liquid epoxy resin, liquid polyester resin, liquid urethane resin, etc. may be used.
[0099] As a liquid plasticizer, for example, a liquid plasticizer for plastics can be used.
[0100] The components contained in the electromagnetic wave absorbing particle dispersion are not limited to the aforementioned electromagnetic wave absorbing particles and liquid medium. The electromagnetic wave absorbing particle dispersion may additionally contain any other components as necessary.
[0101] For example, acid or alkali may be added to the dispersion of electromagnetic wave-absorbing particles as needed to adjust the pH of the dispersion.
[0102] In addition, in order to further improve the dispersion stability of the electromagnetic wave absorbing particles in the aforementioned electromagnetic wave absorbing particle dispersion and to avoid coarsening of the dispersed particle size due to re-aggregation, various surfactants, coupling agents, etc., may be added to the electromagnetic wave absorbing particle dispersion as dispersants.
[0103] The dispersant, such as the surfactant or coupling agent, can be selected according to the application, and it is preferable that the dispersant has one or more functional groups selected from amine-containing groups, hydroxyl groups, carboxyl groups, and epoxy groups. These functional groups adsorb to the surface of electromagnetic wave-absorbing particles to prevent aggregation and have the effect of uniformly dispersing the electromagnetic wave-absorbing particles even within an infrared shielding film formed using the electromagnetic wave-absorbing particles. A polymer-based dispersant having one or more selected from the above functional groups (functional group groups) in its molecule is even more preferable.
[0104] Commercially available dispersants suitable for use include Solspers (registered trademark) 9000, 12000, 17000, 20000, 21000, 24000, 26000, 27000, 28000, 32000, 35100, 54000, 250 (manufactured by Nihon Lubrizol Co., Ltd.), EFKA (registered trademark) 4008, 4009, 4010, 4015, 4046, 4047, 4060, 4080, 7462, 4020, 4050, 4055, 4400, 4401, 4402, 4403, 4300, 4320, 4330. 4340, 6220, 6225, 6700, 6780, 6782, 8503 (manufactured by F-Car Additives), Azisper (registered trademark) PA111, PB821, PB822, PN411, Feymex L-12 (manufactured by Ajinomoto Fine Techno Co., Ltd.), DisperBYK (registered trademark) 101, 102, 106, 108, 111, 116, 130, 140, 142, 145, 161, 162, 163, 164, 166, 167, 168, 170, 171, 174, 180, 182, 192, 193, 2000, 2001, 2020, 2025, 2050, 2070, 2155, 2164, 220S, 300, 306, 320, 322, 325, 330, 340, 350, 377, 378, 380N, 410, 425, 430 (Made by Big Chem Japan Co., Ltd.), Dispalon (Registered Trademark) 1751N, 1831, 1850, 1860, 1934, DA-400N, DA-703-50, DA-725, DA-705, DA-7301, DN-900, NS-5210, NVI-8514L (Kusumoto Kasei One or more types selected from (manufactured by Kabushiki Kaisha), Arpon (registered trademark) UC-3000, UF-5022, UG-4010, UG-4035, UG-4070 (manufactured by Doa Kose Kabushiki Kaisha), etc. may be cited.
[0105] The method for dispersing electromagnetic wave absorbing particles into a liquid medium is not particularly limited as long as it is a method capable of dispersing the electromagnetic wave absorbing particles in a liquid medium. At this time, it is preferable that the average particle size of the electromagnetic wave absorbing particles be 200 nm or less, and it is more preferable that the average particle size be 0.1 nm or more and 200 nm or less.
[0106] As a method for dispersing electromagnetic wave absorbing particles into a liquid medium, examples include dispersion methods using devices such as bead mills, ball mills, sand mills, paint shakers, and ultrasonic homogenizers. Among these, grinding and dispersing using a media-stirring mill, such as a bead mill, ball mill, sand mill, or paint shaker, which uses a media (beads, balls, Ottawa sand), is preferable from the perspective of reducing the time required to achieve a desired average particle size. Through grinding and dispersion treatment using a media-stirring mill, the electromagnetic wave absorbing particles are dispersed into the liquid medium, and simultaneously, micronization proceeds due to collisions between the electromagnetic wave absorbing particles or collisions between the media and the particles, thereby allowing the electromagnetic wave absorbing particles to be further micronized and dispersed. In other words, grinding and dispersion treatment is performed.
[0107] As described above, the average particle size of the electromagnetic wave absorbing particles is preferably 0.1 nm or more and 200 nm or less. This is because if the average particle size is small, the scattering of light in the visible light region with wavelengths of 400 nm to 780 nm or less due to geometric scattering or Mie scattering is reduced. Consequently, it is possible to avoid the electromagnetic wave absorbing particle dispersion, in which the particles are dispersed in a resin or the like and obtained using, for example, the electromagnetic wave absorbing particle dispersion of the present embodiment, becoming frosted like glass and failing to achieve clear transparency. In other words, when the average particle size is 200 nm or less, the light scattering mode of the geometric scattering or Mie scattering weakens and becomes the Rayleigh scattering mode. Since scattered light in the Rayleigh scattering region is proportional to the sixth power of the dispersed particle size, scattering is reduced and transparency is improved as the dispersed particle size decreases. Furthermore, it is preferable that the average particle size is 100 nm or less, as the scattered light becomes very small.
[0108] However, regarding the dispersion state of the electromagnetic wave absorbing particles within the electromagnetic wave absorbing particle dispersion obtained using the electromagnetic wave absorbing particle dispersion of the present embodiment, in which the electromagnetic wave absorbing particles are dispersed in a solid medium such as a resin, as long as a known method of adding the dispersion to the solid medium is performed, the dispersion will not aggregate beyond the average particle size of the electromagnetic wave absorbing particles of the said dispersion.
[0109] In addition, if the average particle size of the electromagnetic wave absorbing particles is 0.1 nm or more and 200 nm or less, it is possible to avoid the electromagnetic wave absorbing particle dispersion or the molded body (plate, sheet, etc.) manufactured having a monotonously reduced transmittance and becoming a grayish color.
[0110] The content of electromagnetic wave absorbing particles in the dispersion of electromagnetic wave absorbing particles of the present embodiment is not particularly limited, but, for example, it is preferably 0.01 mass% or more and 80 mass% or less. This is because sufficient solar radiation transmittance can be achieved by making the content of electromagnetic wave absorbing particles 0.01 mass% or more. In addition, by making it 80 mass% or less, the electromagnetic wave absorbing particles can be uniformly dispersed within the dispersion medium.
[0111] Examples
[0112] The present invention will be explained in more detail below with reference to the examples. However, the present invention is not limited to the following examples.
[0113] Here, the evaluation method in the following examples and comparative examples will first be explained.
[0114] (Chemical analysis)
[0115] Chemical analysis of the obtained electromagnetic wave absorbing particles was performed by atomic absorption analysis (AAS) for Cs and by ICP emission spectroscopy (1CP-OES) for W (tungsten). In addition, O was analyzed using a light element analysis device (LECO, model ON-836), by melting the sample in He gas and quantifying the CO gas that reacted with carbon in the crucible using IR absorption spectroscopy. Table 1 shows the composition ratio calculated with W (tungsten) set to 1, derived from the content ratio of each element obtained by chemical analysis. Furthermore, in the following Examples 1 to 13, a powder of electromagnetic wave absorbing particles containing a cesium-tungsten composite oxide having a W deficiency was obtained. For this reason, for powders A to M, which are electromagnetic wave absorbing particles obtained in Examples 1 to 13, the composition ratio obtained by multiplying the value corresponding to the W deficiency by the composition ratio when W is set to 1 as shown in Table 1 is all the general formula Cs x W 1-y O 3-z(0.2≤x≤0.4, 0 <y≤0.4, 0<z≤0.46)를 충족함을 확인할 수 있다.
[0116] (X-ray diffraction measurement)
[0117] X-ray diffraction measurements were performed by measuring the powder using Cu-Kα rays with the Spectris X'Pert-PRO / MPD instrument.
[0118] Measurements were performed after calibrating the diffraction angles with a standard sample (NIST640e). Then, Rietveld analysis was performed on the obtained XRD diffraction patterns to determine the lattice constants of the crystal phases. In addition, if orthorhombic is included, it is denoted as R in Table 1, and if hexagonal is included, it is denoted as H. In addition, if both orthorhombic and hexagonal are included, it is denoted as R+H in Table 1.
[0119] In the case of the mixed phase of orthorhombic and hexagonal phases, lattice constants for each phase were determined. Then, the orthorhombic lattice constants were converted into hexagonal lattice constants by the following lattice correspondence model. The correspondence of lattice changes between orthorhombic and hexagonal phases is given by Equation 4a, extracted from the model of Solodovnikov 1998 (Non-patent Literature 4). orth 2 +b orth 2 =64a hex 2 =64b hex 2 , c orth =c hex Using, the hexagonal converted lattice constant was calculated. In addition, a in the above equation orth , b orth , c orth represents the lengths of the a-axis, b-axis, and c-axis of an orthorhombic shape. Also, a hex , b hex , c hex represents the lengths of the a-axis, b-axis, and c-axis of the hexagon.
[0120] (Optical properties of electromagnetic wave-absorbing particle dispersions)
[0121] The visible light transmittance (VLT) and solar irradiance transmittance (ST) of the electromagnetic wave-absorbing particle dispersion were measured in accordance with ISO 9050 and JIS R 3106. Specifically, transmittance was measured using a spectrophotometer U-4100 manufactured by Hitachi Seisakusho Co., Ltd., and calculated by multiplying by a coefficient based on the spectrum of sunlight. For transmittance measurement, measurements were taken at 5 nm intervals over a wavelength range of 300 nm to 2100 nm. L * a * b * The color index was calculated by determining the tristimulus values X, Y, and Z for a D65 standard light source and a light source angle of 10° in accordance with JIS Z8701, and then obtaining the color index from the tristimulus values in accordance with JIS Z8729. The RGB color index was calculated from the tristimulus values in the same manner.
[0122] [Example 1]
[0123] Cesium carbonate (Cs2CO3) and tungsten trioxide (WO3) were weighed, mixed, and kneaded in a molar ratio of Cs2CO3:WO3 = 2:11. The resulting mixture was placed in a carbon boat and heated twice at 850°C for 20 hours in an atmospheric tubular furnace to obtain powder A', which is an extremely thin, greenish-white powder. Additionally, when heating, after heating at 850°C for 20 hours, the mixture was removed, ground, mixed, and then reheated under the same conditions.
[0124] The obtained white powder, Powder A', was evaluated as follows.
[0125] The X-ray powder diffraction pattern is slightly Cs6W 11 O 36 It's mixed, but almost Cs4W 11 O 35 It was identified as a single phase (ICDD 00-51-1891).
[0126] The lattice constants were measured as a=14.6733Å, b=52.3841Å, and c=7.7424Å. The related values were very close to those of Solodovnikov (Non-patent Literature 4), a=14.6686Å, b=52.3971Å, and c=7.7356Å. The chemical analysis results of this white powder are Cs 0.36 WO 3.18 This was achieved, and it almost matched the weighing composition.
[0127] Next, TEM observation was performed on the obtained white powder, powder A'. When the limited field electron diffraction pattern was taken, an orthorhombic spot pattern was obtained. Figure 4 shows the spot pattern taken from the c-axis direction of the orthorhombic. Periodicity of b / 8 periods was observed in the b-axis direction, confirming the existence of W and O defect planes. Additionally, from the streaks extending in the b-axis direction, it was found that some plane defects exist on the b-plane. Although this spot pattern from the c-axis is close to 6-fold symmetry, the angle between the (480) and (4-80) spots is 52.2°, which deviates from 60° in the case of 6-fold symmetry, and it is thought that the deviation from 6-fold symmetry is due to the W and O defect planes that entered the b / 8 period.
[0128] The obtained white powder, Cs4W 11 O 35 The powder was spread thinly and evenly in a carbon boat, placed inside a tubular furnace, and heated from room temperature to 800°C in an Ar gas stream. While maintaining the temperature at 800°C, the flow was switched to a mixture of 1 vol% H2 gas (hereinafter, vol% is simply indicated as %) using Ar gas as a carrier, and after reducing for 5 minutes, the H2 gas was stopped and the mixture was slowly cooled to 100°C using only the Ar gas stream. Afterward, the Ar gas stream was stopped and the mixture was slowly cooled to room temperature, and powder A was removed. The color of the removed powder A was aquatic.
[0129] The XRD pattern of powder A exhibited a mixed two-phase pattern of orthorhombic and hexagonal phases. Lattice constants for each phase were determined using the Rietveld method; for the orthorhombic phase, a=14.6609Å, b=52.4040Å, and c=7.7419Å (converted values for hexagonal were a=7.5062Å and c=7.7419Å), and for the hexagonal phase, a=7.4170Å and c=7.5752Å. It was confirmed that the values on the c-axis for both phases fell within the range of 7.560Å ≤ c ≤ 7.750Å.
[0130] Next, TEM observation of powder A was performed, and orthorhombic particles and pseudo-hexagonal particles were observed.
[0131] Here, the electron beam diffraction pattern of a pseudo-hexagonal particle is shown in FIG. 5. The pseudo-hexagonal particle is
[0001] of FIG. 5 HEX As indicated by the electron beam diffraction pattern of the normal axis, it exhibited a diffraction pattern close to hexagonal. Here (200) HEX Wow (110) HEX The interplanar angle was measured to be 59.2°, which was a value close to a hexagon.
[0132] Next, powder A was observed in STEM-HAADF mode (STEM: scanning transmission electron microscopy, HAADF: High-angle annular dark field).
[0133] Figure 6 shows the HAADF image observed from the
[0221] normal axis of a pseudo-hexagonal particle. In the HAADF mode, atomic particles are observed with brightness proportional to the atomic number and the probability of atomic existence in the projection direction, so the (110) that appears dark in Figure 6 HEX The linear region along the line was identified as a defect of W, which has the largest atomic number. The trace of this W defect region was observed from a different direction, (110) HEX It was confirmed that it is spread out in a planar shape. In addition, it is thought that some of the traces with thin contrast are contracted in a linear shape.
[0134] In this embodiment, the heat reduction treatment is performed for 5 minutes, which is shorter than the time described in other embodiments below, and at the beginning of the reduction at high temperature, orthorhombic (010) ORTH The W defect shrinks, causing a structural transition to a pseudo-hexagonal structure, and in the pseudo-hexagonal structure, {100} HEX Many W defect areas during shrinkage could be observed on the surface.
[0135] [Example 2]
[0136] Cs4W, which is powder A' obtained in Example 1 11 O 35 The powder was spread thinly and evenly in a carbon boat, placed inside a tubular furnace, and heated from room temperature to 800°C in an Ar gas stream. While maintaining the temperature at 800°C, the stream was switched to a mixture of 1% H2 gas with Ar gas as a carrier, and after reduction for 15 minutes, the H2 gas was stopped, and the mixture was slowly cooled to 100°C using only the Ar gas stream. Afterward, the Ar gas stream was stopped, and the mixture was slowly cooled to room temperature, and powder B was removed. The color of the removed powder B was blue.
[0137] The XRD pattern of powder B exhibited a mixed two-phase pattern of orthorhombic and hexagonal phases. Lattice constants for each phase were determined using the Rietveld method, yielding a=14.6576Å, b=52.4315Å, and c=7.7412Å for the orthorhombic phase (converted values for hexagonal were a=7.5088Å and c=7.7412Å), and a=7.4122Å and c=7.5940Å for the hexagonal phase. It was confirmed that the values on the c-axis for both phases fell within the range of 7.560Å ≤ c ≤ 7.750Å.
[0138] Next, TEM observation of powder B was performed, and as with powder A obtained in Example 1, orthorhombic particles and pseudo-hexagonal particles were observed. The pseudo-hexagonal particles are
[0001] of FIG. 7 HEXAs indicated by the electron beam diffraction pattern of the normal axis, it exhibited a diffraction pattern close to hexagonal. Here (200) HEX Wow (110) HEX The interplanar angle was measured to be 59.5°, which was a value close to a hexagon.
[0139] [Example 3]
[0140] Cs4W, which is powder A' obtained in Example 1 11 O 35 The powder was spread thinly and evenly in a carbon boat, placed inside a tubular furnace, and heated from room temperature to 800°C in an Ar gas stream. While maintaining the temperature at 800°C, the stream was switched to a mixture of 1% H2 gas with Ar gas as a carrier, and after reduction for 30 minutes, the H2 gas was stopped, and the mixture was slowly cooled to 100°C using only the Ar gas stream. Afterward, the Ar gas stream was stopped, and the mixture was slowly cooled to room temperature, and the powder C was removed. The color of the removed powder C was deep blue.
[0141] The XRD pattern of powder C exhibited a mixed two-phase pattern of orthorhombic and hexagonal phases. Lattice constants for each phase were determined using the Rietveld method, yielding a=14.6649Å, b=52.4010Å, and c=7.7451Å for the orthorhombic phase (converted values for hexagonal were a=7.5064Å and c=7.7451Å), and a=7.4076Å and c=7.6107Å for the hexagonal phase. It was confirmed that the values on the c-axis for both phases fell within the range of 7.560Å ≤ c ≤ 7.750Å.
[0142] Next, TEM observation of powder C was performed, and as with powder A obtained in Example 1, orthorhombic particles and pseudo-hexagonal particles were observed. The pseudo-hexagonal particles exhibited a hexagonal diffraction pattern, as indicated by the electron beam diffraction pattern along the
[0001] axis in Fig. 8. Here (200) HEX Wow (110) HEX The interplanar angle was measured as 60.0°, which became a hexagonal value.
[0143] [Examples 4 to 7]
[0144] Cs4W, which is powder A' obtained in Example 1 11 O 35 The reduction time during the reduction treatment of the powder was changed to 35 to 90 minutes, as shown in Table 1. Except for the above, powders D, E, F, and G were prepared in the same manner as when powder A of Example 1 was prepared. The color tone of powders D to G is all deep blue, and the XRD lattice constants are as shown in the table.
[0145] In addition, as shown in Table 1, in Example 4, an orthorhombic phase was also observed, and the c-axis length converted to a hexagonal phase was 7.7440 Å (Example 4).
[0146] [Examples 8 to 11]
[0147] Cs4W, which is powder A' obtained in Example 1 11 O 35 The heating temperature and reduction time during the heat reduction treatment of the powder were changed as shown in Table 1. Specifically, in Example 8, the time was 650°C for 120 minutes; in Example 9, 700°C for 60 minutes; in Example 10, 900°C for 10 minutes; and in Example 11, 950°C for 20 minutes. Except for the above points, powders H, I, J, and K were prepared in the same manner as when powder A was prepared in Example 1. Water-colored, blue, dark blue, and dark blue powders were obtained, respectively. The lattice constants obtained from the XRD patterns of each obtained powder were as shown in Table 1.
[0148] In addition, as shown in Table 1, in Examples 8 and 9 and the following Examples 12 and 13, an orthorhombic phase was also observed, and the c-axis length converted to a hexagonal phase was 7.7428 Å (Example 8), 7.7471 Å (Example 9), 7.7449 Å (Example 12), and 7.7466 Å (Example 13).
[0149] [Example 12]
[0150] Cesium carbonate and tungsten trioxide were mixed in a molar ratio of Cs2CO3:WO3 = 3:11, spread thinly and evenly in a carbon boat, placed inside a tubular furnace, and heated at 850°C for 5 hours to obtain an extremely thin, greenish-white powder. The main phase of this white powder was Cs6W 11 O 36 Identified with (ICDD1-70-632), but Cs4W 11 O 35 It was a mixed image with.
[0151] The obtained white powder was heat-treated at 800°C for 30 minutes in a 1% H2-N2 stream to obtain a deep blue powder L.
[0152] The XRD pattern of powder L showed a mixed two-phase pattern of orthorhombic and hexagonal. The lattice constants obtained from the XRD pattern of the obtained powder L are as shown in Table 1.
[0153] [Example 13]
[0154] Cesium carbonate and tungsten trioxide were mixed in a molar ratio of Cs2CO3:WO3 = 1:6, spread thinly and evenly in a carbon boat, placed inside a tubular furnace, and heated at 850°C for 5 hours to obtain an extremely thin, greenish-white powder. The main phase of this white powder was Cs4W 11 O 35 and sympathized, but Cs2W6O 19 It was a mixed image with (ICDD00-045-0522).
[0155] The obtained white powder was heat-treated at 800°C for 30 minutes in a 1% H2-N2 stream to obtain a deep blue powder M.
[0156] The XRD pattern of powder M showed a two-phase mixed pattern of orthorhombic and hexagonal. The lattice constants obtained from the XRD pattern of the obtained powder M are as shown in Table 1.
[0157] As shown in Examples 1 to 13 above, white Cs4W 11 O 35 I'm CS6W 11 O 36 , Cs2W6O 19 Cs4W including 11 O 35 When the powder was reduced at a high temperature, the color of the powder gradually changed from watery to blue and dark blue.
[0158] Also Cs4W 11 O 35 It was confirmed that lattice defects containing W defects exist in the phase, and the structure is orthorhombic; however, when this is reduced at high temperature, the lattice defects containing W defects disappear, and the orthorhombic structure changes into a hexagonal structure.
[0159] [Example 14]
[0160] 20 mass% of powder A prepared in Example 1, 10 mass% of an acrylic polymer dispersant having a group containing an amine as a functional group (hereinafter abbreviated as "dispersant a"), and 70 mass% of methyl isobutyl ketone (MIBK) as a solvent were weighed. These weighed materials were placed in a glass container together with silica beads of 0.3 mm diameter, and dispersed and ground using a paint shaker for 5 hours to obtain dispersion A.
[0161] Here, when measuring the average particle size of the electromagnetic wave absorbing particles in dispersion A (the dispersion particle size measured by the ELS-8000 manufactured by Otsuka Denshi Co., Ltd., a particle size measuring device based on dynamic light scattering), it was 26.4 nm.
[0162] This dispersion A was diluted with MIBK to a concentration of 0.05 wt% and placed in a transparent cell with an optical path length of 10 mm. The transmittance was measured using a U-4100 spectrophotometer from Hitachi High-Tech, and the molar absorption coefficient was determined. The profiles are shown in Figs. 9a and 9b. Fig. 9a shows the molar absorption coefficients of the electromagnetic wave absorbing particle dispersions of Examples 14 to 20 and Comparative Example 1, prepared using the electromagnetic wave absorbing particles prepared in Examples 1 to 7. Fig. 9b is a partial enlarged view of Fig. 9a. Fig. 9c shows the molar absorption coefficients of the electromagnetic wave absorbing particle dispersions of Examples 15, 16, 18, 22, 23 and Comparative Example 1, prepared using the electromagnetic wave absorbing particles prepared in Examples 2, 3, 5, 9, and 10.
[0163] According to the profiles shown in Figs. 9a and 9b, absorption in the near-infrared region from 0.6 eV to 1.6 eV and transmission in the visible region from 1.6 eV to 3.0 eV could be confirmed.
[0164] Visible light transmittance (VLT), solar irradiance transmittance (ST), and transmittance at a near-infrared wavelength of 900 nm (T900) were measured as VLT=72.32%, ST=53.28%, and T900=63.2%, respectively, indicating that it is transparent in visible light and also possesses a near-infrared absorption effect. The color index is L * =87.91, a * =-1.26, b * =8.52, and the blue is very weak, resulting in a hue close to a neutral color. Similarly, the RGB indices were R=224, G=220, and B=201, indicating a nearly neutral hue.
[0165] [Example 15]
[0166] Powder B prepared in Example 2 was dispersed and ground in the same manner as in Example 14 to obtain dispersion B. The dispersion particle size was 31.4 nm.
[0167] The measured profiles of the molar absorption coefficients of this dispersion B are shown in FIGS. 9a to 9c. Since the solar irradiation shielding effect and the transmitted color change depending on the VLT value of the dispersion, it is necessary to evaluate the solar irradiation shielding effect and the transmitted color by matching them to the same VLT. Therefore, a transmittance profile was derived from the molar absorption coefficients using the Lambert-Beer equation so that the VLT value was the same as the VLT value of the spectral transmittance of dispersion A obtained in Example 14.
[0168] The optical properties of dispersion B obtained from this conversion were VLT=72.35%, ST=39.84%, and T900=43.7%, respectively, indicating that it possesses extremely good solar radiation shielding characteristics. The transmittance profiles are shown in Figs. 10a and 10b. In addition, the color index is L * =88.04, a * =-3.66, b * = 5.18, and b * This is a positive color, and the blue color is weak, resulting in a hue close to a neutral color. Likewise, the RGB indices were R=217, G=222, and B=208, indicating a hue close to neutral. It was expected that a thin dispersion film of powder B with a VLT of 70 to 80%, used in automotive windshields, would result in a film that gives almost no blue tint.
[0169] [Comparative Example 1]
[0170] Cs4W, which is powder A' obtained in Example 1 11 O 35 The powder was subjected to grinding and dispersion treatment in the same procedure as in Example 14 to obtain dispersion N. The color of dispersion N was grayish-white, and the dispersion particle size of the particles in dispersion N was 30.3 nm.
[0171] The measured profiles of the molar absorption coefficients of dispersion N are shown in FIGS. 9a to 9c. In addition, as in Example 15, a transmittance profile was derived from the molar absorption coefficients using the Lambert-Beer equation so that the VLT value was the same as the VLT value of the spectral transmittance of dispersion A obtained in Example 14.
[0172] The optical properties of dispersion N obtained from this conversion were VLT=72.32% and ST=77.89%, respectively, indicating that there was almost no infrared absorption effect.
[0173] [Comparative Example 2]
[0174] A raw material mixture was prepared by weighing, mixing, and kneading an aqueous solution of cesium carbonate (Cs2CO3), tungstic acid (H2WO4), and tungsten dioxide powder (WO2) to a composition of Cs2O·5WO3·4WO2. After thorough mixing, the raw material mixture was spread thinly and evenly in a carbon boat and maintained at 550°C for 60 minutes under a 1% H2 gas stream using N2 as a carrier. Subsequently, the stream was switched to 100% N2 and maintained for 1 hour, then the temperature was raised to 800°C and maintained for 1 hour, and finally cooled slowly to room temperature to obtain powder O. The color of powder O was deep blue. As a result of chemical analysis, the composition Cs 0.33 WO 2.74 was obtained.
[0175] The XRD pattern of powder O exhibited a hexagonal single phase. Rietveld analysis yielded lattice constants a = 7.4088 Å and c = 7.6033 Å. The value of the lattice constant c-axis was within the desired range.
[0176] Next, TEM observations were performed, and no particularly noticeable lattice defects were observed. In STEM atomic observations as well, no noticeable lattice defects were observed, and no W defects were observed.
[0177] Powder O was subjected to grinding and dispersion treatment in the same procedure as in Example 14 to obtain dispersion O. The color of dispersion O was deep blue. The dispersion diameter of the electromagnetic wave absorbing particles in dispersion O was 25.8 nm. Dispersion O was diluted with MIBK and placed in a transparent cell with an optical path length of 10 mm to measure transmittance and determine the molar absorption coefficient. In the same manner as in Example 15, the transmittance profiles for the same VLT derived by the Lambert-Beer equation using the molar absorption coefficient were shown in Figures 10a and 10b. As for the spectroscopic characteristics at this time, VLT = 72.33%, ST = 35.48%, and the color index L * =88.29, a * =-5.52, b * =-2.89, R=206, G=224, B=217 were obtained. Therefore, dispersion O has a strong near-infrared absorption effect, but b * Since the value is negative and the B value is high, it can be seen that the blue tint is clearly perceived.
[0178] [Comparative Example 3]
[0179] As a reference sample for color tone, a dispersion of In2O3:Sn (hereinafter abbreviated as ITO) with a neutral color tone was prepared. It is known that ITO fine particles possess a neutral color tone, but depending on the reduction or manufacturing method, various types exist ranging from slightly bluish to brownish. Here, among them, ITO powder (Powder P) manufactured by ENAM, which is close to purely transparent, was used.
[0180] Powder P was subjected to grinding and dispersion treatment in the same procedure as in Example 14 to obtain dispersion P. The color of dispersion P was light watery. The dispersion particle size of the electromagnetic wave absorbing particles in dispersion P was 35.4 nm.
[0181] The dispersion P was diluted with MIBK and placed in a transparent cell with a path length of 10 mm to measure the transmittance and determine the molar absorption coefficient. The molar absorption coefficient was derived using the Lambert-Beer equation in the same manner as in Example 15. The transmittance profiles of the derived VLT are shown in FIGS. 10a and FIGS. 10b.
[0182] As for the spectral characteristics at this time, VLT=72.33%, ST=45.94%, T900=46.4%, color index L * =87.78, a * =-2.04, b * =13.68, R=226, G=220, B=191 were obtained. Therefore, the dispersion P using ITO powder is b * It can be seen that the value is a large positive value and since the B value is large, the blue tint is very small and it is perceived as a neutral color. However, regarding the near-infrared absorption effect, it was confirmed to be the same as dispersion B of Example 15 and lower than dispersion O of Comparative Example 2.
[0183] [Examples 16 to 20]
[0184] Powders C to G prepared in Examples 3 to 7 were dispersed and ground in the same manner as in Example 14 to obtain dispersions C to G. Then, dispersions C to G were each diluted with MIBK and placed in a transparent cell with an optical path length of 10 mm to measure transmittance and determine the molar absorption coefficient. In the same manner as in Example 15, the molar absorption coefficient was derived using the Lambert-Beer equation. The dispersion particle size, optical properties, and color index of each dispersion are shown in Table 2, and the profile of the molar absorption coefficient is shown in Figure 9. For these dispersions, it was observed that near-infrared absorption increased as the reduction time at 800°C increased, while the transmitted color showed a stronger tendency toward blue. However, it was confirmed that in all cases, a color tone close to a neutral color was exhibited.
[0185] In the same manner as in Example 15, the transmittance profiles of the dispersions related to Comparative Examples 1 to 3, Example 15, Example 16, and Example 19, calculated so that VLT = 72.3% using the Lambert-Beer formula as the molar absorption coefficient, are summarized and illustrated in FIG. 10a and FIG. 10b. FIG. 10b corresponds to a partially enlarged view of FIG. 10a.
[0186] In addition, the solar transmittance (ST) of the dispersions related to Comparative Examples 1 to 3, Examples 15, 16, and 19 is illustrated in FIG. 11a, T900 in FIG. 11b, and the color index in FIG. 11c and 11d. Furthermore, in FIG. 11a to 11d, t on the horizontal axis R represents the reduction time at 800°C. For this reason, although explanations are provided only for some parts of Figures 11a to 11d, t R This same example becomes the same experimental example.
[0187] In FIG. 10a and FIG. 10b, it can be seen that Comparative Example 1 has a low transmittance of the blue wavelength, while having a high transmittance of the red wavelength, and appears as a transparent film overall when used as a dispersion film (disperse). Conversely, in Comparative Example 2, it has a high transmittance of the blue wavelength, while having a significantly lower transmittance of the red wavelength, and appears as a blue film overall when used as a dispersion film (disperse).
[0188] The dispersions of Examples 15, 16, and 19 are intermediate with the dispersions of Comparative Examples 1 and 2. As the reduction time at 800°C increases, the transmittance of the blue wavelength gradually increases, while conversely, the transmittance of the red wavelength tends to decrease rapidly along with absorption in the near-infrared region. In Example 19, where the reduction time at 800°C is 60 minutes, the transmittance profile approaches that of Comparative Example 2. It can be seen that even with the same VLT value, the electromagnetic wave absorption film of Example 19 has a similar transmittance at the red wavelength but a lower transmittance at the blue wavelength, indicating a more neutral hue.
[0189] In FIG. 11a, it was confirmed that the dispersions of Examples 16 and 19, in which the reduction time at 800°C exceeded 20 minutes, exhibited superior characteristics in terms of solar irradiation shielding effect compared to the dispersion of Comparative Example 3 using ITO. Furthermore, when the reduction time at 800°C was 60 minutes, the conventional Cs 0.33 It is at almost the same level as the dispersion of Comparative Example 2 using WO3.
[0190] Regarding the color tones illustrated in Figs. 11c and 11d, b when the reduction time at 800°C is up to about 30 minutes * The value or B value is Cs 0.33 It can be seen that it is significantly improved, as the value is larger than that of Comparative Example 2 using WO3 and is on the neutral side.
[0191] [Examples 21 to 24]
[0192] Powders H to K prepared in Examples 8 to 11 were dispersed and ground in the same manner as in Example 14 to obtain dispersions H to K.
[0193] The dispersion particle size, optical properties, and color index of these dispersions are shown in Table 2, and the profile of the molar absorption coefficient is shown in Fig. 9c. For these dispersions, although the reduction temperature and time at 650°C to 950°C differ, it can be seen that as the degree of high-temperature reduction of the particles increases, near-infrared absorption increases, while the transmitted color shows a stronger tendency toward blue. However, it was confirmed that in all cases, a color tone close to a neutral color was exhibited.
[0194] It was confirmed that the blue tendency of the transmitted color and the near-infrared absorption effect have a trade-off relationship, and that it is desirable to select an appropriate degree of high-temperature reduction depending on the application.
[0195] [Examples 25, 26]
[0196] Powder L and powder M prepared in Examples 12 and 13 were dispersed and ground in the same manner as in Example 14 to obtain dispersion L and dispersion M.
[0197] The dispersion particle size, optical properties, and color index of these dispersions are shown in Table 2. In these dispersions, the composition and structure of the raw powder were Cs6W 11 O 36 , or Cs2W6O 19 Cs4W including 11 O 35 Although slightly different from the powder, the change from orthorhombic to hexagonal accompanied by high-temperature reduction basically contains the same content, and it is thought that the characteristics of the electromagnetic wave absorption film depend mainly on the reduction conditions at high temperatures.
[0198] In other words, even if the raw material powder is changed between tungsten oxide Cs2O·nWO3 (3.6≤n≤9.0) containing Cs and W, it can be seen that as the degree of high-temperature reduction of the particles increases, the near-infrared absorption increases, while the transmitted color shows a stronger blue tendency. The blue tendency of the transmitted color and the near-infrared absorption effect are in a trade-off relationship, and an appropriate degree of high-temperature reduction can be selected depending on the application.
[0199]
[0200]
[0201] Although electromagnetic wave absorbing particles, an electromagnetic wave absorbing particle dispersion, and a method for manufacturing electromagnetic wave absorbing particles have been described above in the embodiments and examples, the present invention is not limited to the above embodiments and examples. Various modifications and changes are possible within the scope of the gist of the present invention as described in the patent claims.
[0202] This application claims priority based on Japanese Patent Application No. 2020-015756 filed with the Japan Patent Office on January 31, 2020, and incorporates the entire contents of Japanese Patent Application No. 2020-015756 into this international application.
Claims
Claim 1 General formula Cs x W 1-y O 3-z (0.2≤x≤0.4, 0 <y≤0.4, 0<z≤0.46)로 표시되고, 사방정 또는 육방정의 결정 구조를 구비한 세슘텅스텐산화물을 함유하는 전자파 흡수 입자이며,상기 전자파 흡수 입자를 액상 매체에 분산시킨 전자파 흡수 입자 분산액에 대하여, JIS Z8701에 준거하여, D65 표준 광원, 광원 각도 10°에 대한 삼자극값 X, Y, Z를 산출하고, 삼자극값으로부터 JIS Z 8729에 준거하여 구한 b*값이 정의 값인 전자파 흡수 입자. Claim 2 In claim 1, the cesium tungsten oxide is an electromagnetic wave absorbing particle having linear or planar defects on one or more selected planes, such as the (010) plane of the orthorhombic structure, the {100} plane of the hexagonal prism, and the (001) plane of the hexagonal bottom. Claim 3 An electromagnetic wave absorbing particle according to claim 1 or 2, wherein the cesium tungsten oxide has a defect, and the defect includes a tungsten defect. Claim 4 An electromagnetic wave absorbing particle in which a portion of the O of a WO octahedron constituting the orthorhombic or hexagonal crystal of the cesium tungsten oxide is randomly missing, according to claim 1 or 2. Claim 5 In claim 1 or 2, the cesium tungsten oxide is an electromagnetic wave absorbing particle having a c-axis length in hexagonal conversion of 7.560 Å or more and 7.750 Å or less. Claim 6 An electromagnetic wave absorbing particle according to claim 1 or 2, wherein a portion of the Cs of the cesium tungsten oxide is substituted by an additive element, and the additive element is one or more types selected from Na, Tl, In, Li, Be, Mg, Ca, Sr, Ba, Al, and Ga. Claim 7 The electromagnetic wave absorbing particle according to claim 1 or 2, wherein the average particle size of the electromagnetic wave absorbing particle is 0.1 nm or more and 200 nm or less. Claim 8 An electromagnetic wave absorbing particle according to claim 1 or 2, wherein the surface of the electromagnetic wave absorbing particle is modified by a compound comprising one or more atoms selected from Si, Ti, Zr, and Al. Claim 9 Electromagnetic wave absorbing particles according to claim 1 or 2, which are particles obtained by heating and reducing a crystal powder of a cesium tungsten oxide precursor nCs2O·mWO3 (n, m are integers, 3.6≤m / n≤9.0) in a reducing gas atmosphere at a temperature of 650°C or higher and 950°C or lower. Claim 10 In paragraph 1 or 2, Cs4W as the main component 11 O 35 Electromagnetic wave absorbing particles obtained by heating and reducing a cesium tungsten oxide precursor containing a phase at a temperature of 650°C or higher and 950°C or lower in a reducing gas atmosphere. Claim 11 An electromagnetic wave absorbing particle dispersion comprising an electromagnetic wave absorbing particle described in claim 1 or 2 and one or more liquid media selected from water, organic solvent, oil, liquid resin, and liquid plasticizer, wherein the electromagnetic wave absorbing particle is dispersed in the liquid media. Claim 12 In claim 11, an electromagnetic wave absorbing particle dispersion having a content of the electromagnetic wave absorbing particles of 0.01 mass% or more and 80 mass% or less. Claim 13 A method for manufacturing electromagnetic wave absorbing particles according to claim 1 or 2, comprising: a heating and reduction process in which a crystal powder of a cesium tungsten oxide precursor nCs2O·mWO3 (n, m are integers, 3.6≤m / n≤9.0) is heated and reduced in an atmosphere of reducing gas at a temperature of 650°C or higher and 950°C or lower; and a grinding process in which the powder obtained by the heating and reduction process is ground.
Citation Information
Patent Citations
Near-infrared absorbing fine particle dispersion liquid and method for producing the same
US20180016460A1
